Identification of neutralization and diagnostic epitopes on PIM, the polymorphic immunodominant molecule of Theileria parva - Toye, Philip G.; Nyanjui, J.; Goddeeris, Bruno M.; Musoke, A.J. (1996)
The polymorphic immunodominant molecule (PIM) of Theileria parva is expressed by the schizont and sporozoite stages of the parasite. We have recently cloned the cDNA encoding the PIM antigen from two stocks of the parasite: the cattle-derived T. parva (Muguga) stock and a buffalo-derived stock. The cDNAs were used in transient-transfection assays to assess the reactivity of the antigen with monoclonal antibodies (MAb) previously raised against schizont-infected cells and used for parasite strain identification. We demonstrate that 19 of the 25 MAb are specific for PIM. Antibody reactivities with deletion mutants of a fusion protein containing PIM and Pepscan analysis of the Muguga version of the molecule with 13 of the MAb indicate that there are at least 10 different epitopes throughout the molecule. None of the MAb react with a tetrapeptide repeat present in the central region of the molecule, probably because of an inability of BALB/c mice to produce antibodies to this repeat. In contrast. sera from infected cattle react strongly wityh the repeat region, suggesting that this region alone may be useful as a diagnostic reagent. Previous studies showed that MAb to PIM inhibit sporozoite infectivity of bovine lymphocytes in vitro, which suggests that the antigen may be useful in immunizing cattle against T. parva infection. Pepscan analysis revealed that sera from infected cattle reacted with peptides recognized by the neutralizing MAb, as did sera from cattle inoculated with a PIM-containing recombinant protein. The latter sera did not, however, neutralize sporozoite infectivity in vitro. These results will be useful in exploiting the strain identification, diagnostic, and immunizing potentials of this family of antigens.